PENDAMPINGAN PEMBUATAN ANGGARAN RUANG SERBA GUNA RT 02 DESA RAWA MEKAR JAYA - Rasyid, Rosmita; Puswita Anhar, Dela Asokawati; Puspita, Elizabeth Christinio (Transpublika Publisher, 2023)
The purpose of this community service activity is to assist in assisting the preparation of budgets and the realization of the construction of a multi-purpose room that will be used for the public interest of RT. 02 residents of Rawa Mekar Jaya village, Serpong District, South Tangerang, Rawa Mekar Jaya Village was chosen as a partner for community service activities due to the lack of knowledge and supervision of residents in the neighborhood towards budgeting for certain public facility projects. Based on initial observations to partners conducted by direct visits, the main problem lies in the absence of budgeting experts who do not participate in the budgeting of multi-purpose rooms. Meanwhile, public facility projects such as multi-purpose rooms must be planned carefully and accurately because they are related to the rights and interests of all residents. The method that will be used in this community service activity is assistance through training/socialization regarding offline and online budgeting. Through this community service activity, it is hoped that public facilities in the form of a multipurpose room for RT. 02 residents of Rawa Mekar Jaya Village can be built with the right, efficient and accurate budget. Thus, it is hoped that in the future the function room can be useful and used for the common interests of local residents.